Circulating cell-free nucleic acids of plasma in human aging, healthy aging and longevity: current state of knowledge - Tessier, Nicolas P.; Hardy, Lise M.; Deleuze, Jean-François; How-Kit, Alexandre (Frontiers in Genetics, 2023)
Circulating cell-free nucleic acids (ccfNAs) of plasma are a remarkable source of genetic, epigenetic and transcriptomic materials originating from different cells, tissues and organs of an individual. They have been increasingly studied over the past decade as they can carry several important pieces of information about the health status of an individual, which makes them biomarkers of choice for non-invasive diagnostic of numerous diseases and health conditions. However, few studies have investigated variations of plasma ccfNAs in healthy subjects, particularly in relation to aging, healthy aging and longevity, despite the great variability of these biological processes among individuals. Here, we reviewed several studies that focused on the analysis of circulating cell-free DNA (ccfDNA) and microRNAs (ccfmiRNAs) during aging and in the elderly, including some on exceptionally long-lived individuals, i.e. centenarians. After a brief overview of the types, origins and functions of plasma ccfNAs, we described the variations of both ccfDNA and ccfmiRNAs during aging as well as the identification of several potential ccfDNA-based and ccfmiRNA-based biomarkers of aging, healthy aging and/or longevity. We finally highlighted some prospects offered by ccfNAs for the understanding and improvement of healthy aging and longevity.